Robert B. Parker's Blind spot [compact disc, unabridged] - Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Jesse Stone novels., 2014)
When Jesse is invited to a reunion of his old Triple-A team, he is forced to grapple with his memories and his regrets over what might have been. But his time at the reunion is cut short when a young woman is found murdered and her boyfriend, a son of one of Paradise's most prominent families, is missing and presumed kidnapped. There is a connection between the reunion and the crimes as Jesse discovers that one of his former teammates may in fact be his main suspect.